Construção e montagem de uma plataforma de testes de baixo custo para apoio à pesquisa em Vant’s - Lucena Júnior, Ubiracui Pereira de (Universidade Federal Rural do Semi-Árido, 2017)
Researches with VANT (Unmanned Aerial Vehicle) have developed due to technological advances, and gained space in military and civilian applications such as surveillance, photographs of difficult to reach places or in situations of human risk. Analyzing this growth, a test platform for research with VANT (Unmanned Aerial Vehicle) was developed in the proposed work. The VNA used in the research was a quadratic type that has six degrees of freedom, that is, it has the ability to perform movements on the x, y and z axes, as well as movements around these axes known as pitching, pitch, roll, θ) and yaw (yaw, ψ) respectively. The material used for fabrication and assembly is low cost. Initially, the platform was simulated through the SolidWorks® software with the preview of the prototype for the best sizing. The second step was the fabrication and assembly of the platform components using the welding and mechanical equipment, such as: lathe and sawing tape. The entire manufacturing process was carried out in the mechanical production laboratory of the Federal Rural Semi-Arid University (UFERSA). For the validation of the platform, a test was performed simulating a flight plan in order to adjust the speed of the motors of the quadricopter. During the tests different speeds were applied in the motors, thus obtaining different rotational movements around their axes. It was verified that the quadricopter was able to move freely in the six degrees of freedom. Finally, in this context the practical study had its objective reached, the manufacture of a low cost metal platform, with good mechanical resistance and good performance with dynamic loads.
Monografia
Keywords: Plataforma; VANT; Baixo custo; Processo de fabricação; Platform; VANT's; Low Cost; Manufacturing Process; ENGENHARIAS::ENGENHARIA MECANICA